Determining Factors in SMEs Innovation Performance: An Empirical Study in Indonesia - Tri Siwi Agustina; Muhammad Ega Patria Arganata (Forum Inovasi Bisnis dan Manajemen, 2023)
In today’s business world, innovation performance is widely acknowledged as an essential factor in enhancing business performance. Therefore, the present study attempts to identify and examine the factors that may enhance the innovation performance of SMEs in the creative industry. More specifically, the research aims to explore the relationship of entrepreneurial orientation, knowledge management and collaborative innovation activities with innovation performance. The study empirically examines this conceptual model using a sample of 32 business owners in Small and Medium Enterprises (SMEs) Centers of Wallet and Bag Production in Mojokerto, East Java, Indonesia. PLS-SEM technique has been applied in data analysis and the SmartPLS 3.0 software is used to test the study hypotheses. The results indicate that entrepreneurial orientation and knowledge management has a direct effect on collaborative innovation activities. Similarly, the relationship of collaborative innovation activities and innovation performance is* also found to be significant. The findings also show the indirect effect of entrepreneurial orientation and knowledge managemen on innovation performance through collaborative innovation activities. The research implications, limitations and future research directions are highlighted in the concluding sections of the study.